HEAT CAPACITY OF SOLIDS. DULONG - PTI LAW. EINSTEIN-DEBAY THEORY - Xatamov Xumoyun Isroilovich,; Usmonov Isroiljon Muxtorjon o’g’li,; Xatamova Durdona Ahadjon qizi, (Zeta Repository, 2023)
This article discusses the heat capacity of solids. Data on the Dulong-Pti and Einstein- Debay theories in the calculation of the heat capacity of solids in the field of high and low temperatures are given.